Adapting and Validating the SERPVAL Scale in Higher Education Service Experience - Wan Mustaffa, Wan Salmuni; Ali Hamid, Mass Hareeza; Bing, Khuan Wai; Abdul Rahman, Rafiduraida; Ab Wahid, Hariyaty (International Business Education Journal, 2015)
Drawing on Means-End Chain (MEC) theory, service information is retained and evaluated in the customers’ cognitive at three levels of abstraction namely, Service Personal Values (the highest level); Service Value; and Service Quality (the lowest level). Although the lowest levels have been extensively investigated particularly through SERVQUAL model, there is a clear research gap at the highest level of abstraction. The limitation of investigating the highest level of abstraction is due to its individuality and complexity in comparison to the other levels. In 2005, Lages and Fernandes have developed the SERPVAL scale to measure the customers’ cognitive based on their individual values in telecommunication service experience. However, the scale still needed further validation in other types of services including higher education to establish its generalizability. Thus, the main objective of this research is to validate the SERPVAL scale in higher education context. In this research, the postgraduate international students (PIS) at Malaysian research universities were selected as sample elements. The data was gathered through online survey. The online questionnaire was sent to PIS emails following the proportionate stratified sampling technique. The Confirmatory Factor Analysis (CFA) measurement model using AMOS 18.0 was performed to validate the SERPVAL scale. The findings reveals that SERPVAL scale achieved unidimensionality, validity and reliability which presented by the Cronbach Alpha>0.70; Construct Reliability (CR)>0.60; Average Variance Extracted (AVE)>0.50 and the fitness indexes have achieved the required levels. This research concluded that SERPVAL is an accurate scale to measure personal values in higher education context. The theoretical and managerial implications as well as the directions for future research are also discussed.